The incidence of non-tumour diseases of the respiratory organs of offspring of the first generation of residents of radiation-contaminated territories of Ukraine under the age of 18 years - Yaroshenko, Zh. (Journal of Education, Health and Sport, 2019)
There was conducted an epidemiological study of the morbidity of non-tumour diseases of the respiratory organs of the first-generation offspring born by residents of radioactively contaminated territories, until they reached 18 years. The observation period from 1987 to 2016. The total cohort was 35893 individuals, among whom male offspring constituted 18138 individuals, while female offspring constituted 17755 individuals. There were created 4 groups to study offspring up to 3 years old, depending on the time of birth of offspring after an accident – years of birth:(first – 01.03.1987– 28.02.1990, second – 01.03.1990– 28.02.1993, third – 01.03.1993– 28.02.1996, fourth – 01.03.1996– 28.02.1999), with a three-year observation period. During the observation period, there were detected 7845 cases of non-tumour respiratory diseases, which is 36.6% of the total pathology and 59,59±0,65 cases by 103 man-years observations. Of whom male offspring 4146 cases (С –38,8%, ID–62,42±0,94 by 103 man-years), and female offspring – 3699 (С –34,6%, ID– 56,72±0,91). The formation of non-tumour respiratory diseases occurred mainly due to the groups of diseases: "acute respiratory infections of the upper respiratory tract" (J00-J06.9) and "influenza and pneumonia" (J10-J18.9), "other upper respiratory tract diseases (J30.0-J39.9)" and "other acute respiratory infections of the lower respiratory tract (J20- J22), which amounted to 98.84%. For all the years of observation among the studied groups, the highest rates of respiratory disease in each period on the first or second, and the lowest - on the fourth. An analysis of the incidence showed that up to 6 years, offspring were mainly affected by acute respiratory infections of the upper respiratory tract and chronic tonsillitis and adenoids, and in the younger school-age, the incidence increased due to acute upper and lower respiratory tract diseases. In adolescence, the morbidity of the respiratory system is complicated by more severe nosological forms: chronic obstructive pulmonary disease, asthma.